FAKTOR RISIKO DOMINAN TERJADINYA STUNTING PADA ANAK USIA 6-23 BULAN DI PERDESAAN DAN PERKOTAAN DI PROVINSI SUMATERA BARAT (ANALISIS DATA SSGI 2022) - Wahyuningrum, Marlina Rully; Utari, Diah Mulyawati (Poltekkes Kemenkes Bandung, 2025)
Stunting is low in length or height for age due to chronic malnutrition. Stunting disrupts growth and development. West Sumatera is the only province in Sumatera that has increased stunting in 2022. The high stunting in rural compared to urban is related to the determinants of stunting in that region. This study aims to analyze the dominant risk factor of stunting in children aged 6-23 months based on rural-urban in West Sumatera according to the Indonesian Nutrition Status Survey 2022. This research design is cross-sectional with a sample size of 2,011 children in West Sumatera. This research was analyzed univariate, bivariate (chi-square), and multivariate (multiple logistic regression). The results show that stunting in West Sumatera is 18.4%, with stunting in rural (22.1%) higher than urban (16.8%). There are differences in stunting proportion based on gender, child's age, birth length, mother's height (rural, urban, West Sumatera); ANC visit (rural, West Sumatera); pneumonia, birth weight, maternal education, household food security, sanitation (urban, West Sumatera); classification of residence (West Sumatera). The dominant risk factor of stunting is the mother's height <150 cm in rural, urban, and West Sumatera (OR=3.024; 3.068; 2.941). Mothers with short height have bad eating habits until when feeding their children, resulting in children's nutritional needs not being met, so the risk of stunting increases. These results can be used as evaluation and recommendations for all parties that prevent stunting, starting from the upstream with more attention to nutritional intake and the health of children and pregnant women.